Characteristics of Pedestrian Flow at Traffic Signalised Crossing in Shah Alam - Abdullah, Ahmad Syakirin; David Daniel, Basil (Recent Trends in Civil Engineering and Built Environment, 2021)
Pedestrians are among the contributors to road traffic accidents and are identified as vulnerable users to accidents. There are a number of factors that cause accidents among pedestrians and road users to be studied, so that the safety of road users especially pedestrians can be improved. The study was conducted to identify pedestrian characteristics in terms of gender, group, and time span in crossing roads. Therefore, a study of pedestrians in the pedestrian crossing area was conducted. In this study, the study area is the main urban road at Shah Alam, Selangor. This study is important to provide an accurate picture of the characteristics of pedestrian flows along the pedestrian crossing in Shah Alam. The study area was selected based on two main focus areas of pedestrian crossing. The first area is at the SACC Mall and the second area at Perdana Apartment near the Shah Alam Stadium. Characteristics of pedestrian flow along pedestrian crossing are identified through observation methods in the study area using video recordings to track pedestrian volumes and group categories. Based on the data obtained, the analysis was performed to achieve the objective of the study to determine the volume of pedestrian, pedestrian gender and pedestrian category by personal, couple or grouping in pedestrian crossing road. In addition, this study was performed to determine the start loss time and clearance time gain of pedestrians. In conclusion, all the factors of pedestrians in making crossing at traffic crossings in terms of gender, crossing method, and the time taken to affect the speed of pedestrians in making a crossing at traffic crossings. at peak times and non-peak times. Also, the average for the speed of each class category is very significant in making crossings.